Design and analysis of relay-selection strategies for two-way relay network-coded DCSK systems - Cai, Guofa (2020)
This paper investigates a two-way two-relay network-coded differential-chaos-shift-keying (DCSK) system over multipath Rayleigh fading channels. First, a decode-and-forward protocol is considered, when the two relays first decode the two users' orthogonal transmitted signals and then forward their XORed version back to the users. Based on the equal-gain-combining method at the receiver of each user, the bit-error-rate (BER), achievable diversity order, and throughput are analyzed. It is shown that, as compared to the conventional two-way one-relay network-coded DCSK system, the proposed system achieves lower BER, but reduces the throughput meanwhile. To improve the overall performance and avoid the throughput loss, a novel relay-selection criterion is developed based on the decision metrics used for conventional symbol detection, which can be implemented without requiring the channel state information. According to the criterion, three relay-selection strategies are suggested, namely the max-sum, max-product and max-min relay selections. Both analytical and simulated results show that the proposed relay-selection strategies significantly improve the BER and throughput of the two-way two-relay network-coded DCSK system and achieve higher diversity order. As a further insight, the superiority of the proposed relay-selection strategies is demonstrated in multirelay scenarios. Overall, the proposed system stands out as a promising candidate for low-power and low-complexity short-range wireless-communication applications, such as wireless sensor networks.